Model Pembelajaran Rolex Berbantuan Media Boneter Meningkatkan Keaktifan dan Keterampilan Berbicara Teks Descriptive - Arisandi, Yuli (Jurnal Didaktika Pendidikan Dasar, 2021)
The research was aimed at improving the student’s activeness and speaking skill by using role exchange model and character doll media. The research consisted two cycles.The procedures were: planning, implementation, observation and reflection. The study used two data. The qualitative data through observation the student’s activeness in learning process.The quantitative data were obtained by speaking test performance. The students’ activeness with high score in preliminary observation reached 5 students (17,86%) improved 23 students (82,14%) in Cycle II. It can be seen that all students paid attention their teacher, engaged in problem solving and applied they learned. Most of them also had ideas and gave the questions. The data of the speaking skill assessment in preliminary observation showed that 42,85% (12 students) got the same score or above KKM with the average 61,77 increased 89.29% (23 students) with the average score was 77.3 in second cycle. Improvement was significant especially in student’s vocabulary mastery, comprehension and fluency. While, grammar and pronunciation improved although was not significant. The conclusion of this research is that: (1) the students’speaking skill improves from the previous condition, first cycle and then second cycle; 2) the students’ activeness in English teaching learning also improves.